Análise dos impactos produtivos e competitivos do Programa RHAE-Inovação em pequenas e médias empresas - Silva, Armando Paulo da (2005)
This work has as its objective to present the analysis of the productive and competitive impacts of the RHAE-Innovation program in small and average companies paranaenses. To base the research, it was necessary a bibliographical revision involving the diverse classifications of the companies; the concepts of science, technology and innovation; the questions of the barriers and factors which facilitate the innovation and a brief summary of the politics of incentives to the PMES, emphasizing the distribution of resources between companies and universities and/or institutes of research. This analysis was based on the criteria which the CNPq uses for the selection of the projects and on the indicators of innovation, R&D and human resources of agencies of national and international reference. The results gotten in this research point that the RHAE-Innovation Program is an important source of resources for the PMEs. Another important factor related to the objective of the program in inserting researchers in the productive atmosphere with a better scientific technique capacity. In this way it is necessary that the criteria used in the selection are appraised to each edition, mainly in relation to P&D in order to verify the marketing viability of the products and/or better or new processes. In relation to the productive and competitive impacts that the program generates in PMEs they depend on the reality of the company and of their managers' culture.